The Grants Register 2022 The Complete Guide to Postgraduate Funding Worldwide - Palgrave Macmillan; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2021)
The Grants Register 2022 is the most authoritative and comprehensive guide available of postgraduate and professional funding worldwide. It contains international coverage of grants in almost 60 countries, both English and non-English speaking; information on subject areas, level of study, eligibility and value of awards; and information on over 6,000 awards provided by over 1,300 awarding bodies. Awarding bodies are arranged alphabetically with a full list of awards to allow for comprehensive reading. The Register contains full contact details including telephone, fax, email and websites as well as details of application procedures and closing dates. It is updated annually to ensure accurate information.
Preface -- How to Use The Grants Register -- The Grants Register -- Subject and Eligibility Guide to Awards -- Index of Awards -- Index of Discounted Awards -- Index of Awarding Organizations.
Keywords: Professional education; Vocational education; Continuing education; Professional and Vocational Education; Lifelong Learning